Mountain of fire - Cordova, Jason, 1978- (Cordova, Jason, 1978- Black tide rising., 2025)
"When the lights went out, humanity died. But from darkness came hope. The surviving students at St. Dominic's Preparatory School for Girls have had it rough since the H7D3 virus virtually wiped out human civilization. Between rampaging hordes of zombies and wannabe tinpot dictators, the only thing holding them together is the iron will of the school's lone surviving nun, Sister Ann. They know how to survive, but rebuilding isn't only about surviving-it's about rising up. As more survivors start to seek asylum at the isolated school, it becomes readily apparent that the school can be the anvil from which humanity is reforged. To achieve this, though, the survivors must rely on one another to rebuild. The flames of life will be fanned, and the sparks from every strike of the hammer will provide light in the darkness. But it will not be easy"--